REFLECTION OF ECO-HUMANIST ATTITUDE IN THE EPOS «MANAS» (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2022)
This article deals with the philosophical works of oral ecological values; the great mind conconant with ecological imperatives of our time, the distribution of theirfuture generations and the formation of ecological culture.
Keywords: epic «Манас», eco-culture, nomads, ecological, content, essense.